(untitled) (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
Employee performance is the result of work in quality and quantity achieved by an employee in carrying out his duties in accordance with the responsibilities given to him by the company. The purpose of this study was to determine the effect of motivation, communication, and physical work environment on employee performance at CV. Bali Stars Promosindo. Questionnaires that have been tested for validity and reliability were given to 42 respondents. The data analysis technique used in this study is the Classical Assumption, Coefficient of Determination, Multiple Linear Regression, T-Test and F-Test. 0.000. (2) Communication has a significant positive effect on employee performance, where the t value is 4.498 and sig 0.000. 3) Physical Work Environment has a positive and significant effect on employee performance, where the t value is 5.295 and sig 0.000. Simultaneously, motivation, communication, and physical work environment have a significant effect on employee performance, where the f value is 466.237 and the significance is 0.000. The magnitude of the influence of Motivation, Communication, and Physical Work Environment on Employee Performance is 97.4%.